Efektivitas Model Pembelajaran Flipped Classroom terhadap Peningkatan Motivasi Belajar Siswa pada Mata Pelajaran Sejarah di SMAN 2 Bandung - Haq, Muhammad Juraisy; Kurniawan, Deni; Mulyadi, Dadi (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2025)
Background of this research is low student motivation in history lesson. This is caused by monotonous learning, which makes students bored.This study aims to determine how effective the flipped classroom model is in enhancing learning motivation, particularly in history lessons. A quantitative approach was employed using a quasi-experimental method with a non-equivalent control group design. The sample consisted of class XI-K as the experimental group and class XI-J as the control group. Data were analyzed using the Wilcoxon Sign Rank Test and the Mann-Whitney U Test. The results revealed an increase in learning motivation within the experimental class. These findings highlight that the flipped classroom model is effective and can be applied to improve students’ learning motivation, especially in the context of history education.